A comparison of loupe-assisted and non-loupe-assisted subinguinal varicocelectomy - Chike John Okeke; Rufus Wale Ojewola; Emmanuel Ajibola Jeje; Kehinde Habeeb Tijani; Moses Adebisi Ogunjimi (Nigerian Postgraduate Medical Journal, 2023)
Introduction: Varicocele is a treatable aetiology of male infertility. Magnification with surgical loupe has been associated with improved outcome and reduced morbidity than the conventional technique without magnification. Objective: To compare the outcomes of two techniques of subinguinal varicocelectomy, with a surgical loupe and without. Patients and Methods: This was a prospective randomised hospital-based study. Forty-six patients were randomised to two arms – Group A: loupe-assisted subinguinal varicocelectomy (LASV) and Group B: open subinguinal varicocelectomy without Loupe (OSV). They all had their semen and hormonal parameters compared preoperatively and at 3 and 6 months postoperatively. Post-operative complications were also assessed. P < 0.05 was considered statistically significant. Results: The mean age was 38.28 ± 4.55 years with a range of 27–46 years. The mean age in Group A was 37.35 ± 4.68 and 39.22 ± 4.33 years in Group B. There was an improvement in motility, sperm count and concentration in both the groups at 3 and 6 months (P < 0.05). However, there was no difference in these parameters on comparison of the two groups at 3 and 6 months (P > 0.05). Follicle-stimulating hormone decline was significant in the OSV group at 3 and 6 months, P = 0.010 and 0.021, respectively. There was no difference in other hormonal parameters both at 3 and 6 months (P > 0.05). The pregnancy rate in each arm of study was 4.3%. All complications occurred in Group B. Conclusion: Both techniques resulted in improvement in seminal fluid parameters. All complications occurred in the arm that had subinguinal varicocelectomy without loupe. Loupe-assisted subinguinal varicocelectomy is safe and effective.